O uso/não uso de preservativo entre mulheres residentes em Belo Horizonte e Recife, 2002: um estudo de fatores associados - Claudia Ferreira Souza (2008)
Sexually transmitted diseases (STD's), including the Human Immunodeficiency Virus (HIV), are major causes of morbidity, mortality, and disability. They are also associated with high costs for public health systems. Among the various forms of prevention, the use of condoms has gained increasing importance and is described as an effective way to reduce STD's/AIDS infection and unwanted pregnancies. The objective of this master´s thesis is to investigate associations between the use and non-use of condom and education level, age, race/color and region of residence (Belo Horizonte and Recife) among white, brown, and black females of three different cohorts: young (18-29), adult (30-39) and mature (50-59).Data come from the survey SRSR Reprodutive Health, Sexuality, and Race/Color, a survey carried out by Cedeplar in Belo Horizonte and Recife in 2002. I use descriptive analysis and univariate logistic regressions to estimate the odds of not using a condom for females of the three cohorts under study, using as covariates social; sexual behavior; knowledge, perception and information; health care; and empowerment factors.The odds of not using condoms is higher among women from Recife, if compared to those who live in Belo Horizonte; for the mature cohort, if compared to the young cohort the risk for adult women is in between for whites, if compared to brown and black; for the less educated. If compared to the more educated females.